Recent Advances in Photocatalytic Removal of Microplastics: Mechanisms, Kinetic Degradation, and Reactor Design - Hamd, Wael; Daher, Elie A.; Tofa, Tajkia Syeed; Dutta, Joydeep (Frontiers in Marine Science, 2022)
Plastic products are used in almost all aspects of our daily life. Due to their low cost, portability, durability, and resistance to degradation, these products are affecting the health of the environment and biota on a global scale. Thus, the removal and mineralization of microplastics is an important challenge in the 21st century. Advanced oxidation processes (AOPs) have recently been identified as a viable treatment technique for tackling recalcitrant organic molecules and polymers. However, information on kinetic degradation mechanisms and photocatalytic reactor design is insufficient. This review discusses the fundamentals of photocatalysis and photo-Fenton processes in addition to the photocatalytic degradation mechanisms. We also introduce different characterization techniques of the major microplastic pollutants such as PE, PP, PVC, PS, PMMA, and PA66. In addition, a detailed overview of the major existing photocatalytic plants and the scaling-up methods of photoreactors are discussed.